Sustainable management of water hyacinth (Eichhornia crassipes): Community-Led strategies for livelihood enhancement in rural India - Aji Abba; Sabarinath S (Results in Engineering)
Water hyacinth (Eichhornia crassipes) threatens water quality, ecosystem health, and livelihoods in wetland ecosystems. Despite various control efforts, its rapid proliferation intensifies water contamination and economic hardships. The current study assesses its environmental and socio-economic impacts while exploring sustainable, community-driven management strategies. A Convergent Parallel Mixed-Methods Design was employed, integrating water quality analysis, household surveys (n = 189), key informant interviews (n = 14), Quadrant sampler, and Participatory GIS (PGIS) mapping. Physicochemical and microbiological water parameters were analyzed, while socio-economic impacts were assessed through surveys. Statistical analysis was conducted and spatial distribution analysis. Findings indicate pH levels (5.9–6.3), turbidity (>12 NTU), and Escherichia coli contamination exceeding WHO/BIS limits. Water hyacinth coverage ranged from 75 to 94 %, contributing to a 65–70 % decline in fish catch and monthly household income losses of ₹3000. However, 83 % of respondents supported biofertilizer production, highlighting potential for sustainable utilization, particularly in communities facing rising costs of chemical fertilizers. Water hyacinth management requires integrated ecological and economic strategies. Community-led bio-utilization offers a sustainable pathway for mitigation, supporting SDG 6 (Clean Water) and SDG 12 (Sustainable Consumption) and SDG 15 (Life on Land). Future research should assess long-term viability of biofertilizer production and scalability of community-based interventions in similar regions.